“System Conditions”, System Failure, Structural Racism and Anti-Racism in the United Kingdom: Evidence from Education and Beyond - Paul Miller (Societies, 2021)
Racism in any society is fuelled by a number of factors, often acting independently of each other, or, at times, in concert with each other. On the one hand, anti-racism efforts rely on the alignment of four “system conditions” to stand a chance of successfully engaging and tackling racism. On the other hand, where these “system conditions” are not present, or where they are not in sync, this leads to “system failure”—a situation where racism is writ large in society and in the institutions therein, and where anti-racism efforts are severely hampered. Drawing on evidence from within the education sector and elsewhere in UK society, this paper examines how a lack of alignment between “system conditions” hampers antiracism efforts, and simultaneously reinforces racism in society and in institutions—leading to gridlock or “system failure” around anti-racism.